(untitled) (Sociologisk Forskning, 1999)
Unemployment concentration: Caused by negative attitudes towards paid work? This article studies the concentration of unemployment within families and social networks in Sweden. The study, which is based on two random samples, one consisting of approximately 47000 young people and their parents and one consisting of 3500 unemployed persons, raises the question of whether unemployment concentration mainly is caused by negative values towards employment or by structural factors. The results show that it is common for persons who are unemployed and have experienced longer periods of unemployment to have unemployed family members and friends. The causes of the unemployment concentration can be traced to structural factors such as class, ethnicity, age, unemployment rate and population in the district etc., rather than to the attitudes of the members of the unemployed group.